Mindsets and Neural Mechanisms of Automatic Reactions to Negative Feedback in Mathematics in Elementary School Students - Puusepp, Ita; Linnavalli, Tanja; Huuskonen, Milla; Kukkonen, Karoliina; Huotilainen, Minna; Kujala, Teija; Laine, Sonja; Kuusisto, Elina; Tirri, Kirsi (Frontiers in Psychology, 2021)
Neuroscientific research regarding mindsets is so far scarce, especially among children. Moreover, even though research indicates the importance of domain-specificity of mindsets, this has not yet been investigated in neuroscientific studies regarding implicit beliefs. The purpose of this study was to examine general intelligence and math ability mindsets and their relations to automatic reactions to negative feedback in mathematics in the Finnish elementary school context. For this, event-related potentials of 97 elementary school students were measured during the completion of an age-appropriate math task, where the participants received performance-relevant feedback throughout the task. Higher growth mindset was marginally associated with a larger P300 response and significantly associated with a smaller later peaking negative-going waveform. Moreover, with the domain-specific experimental setting we found a higher growth mindset regarding math ability, but not general intelligence, to be associated with these brain responses elicited by negative feedback regarding errors in math. This suggests that it might be important to address domain-specific and even academic-domain-specific beliefs in addition to general mindsets in research and practice.